Integrated analysis of the yeast NADPH-regulator Stb5 reveals distinct differences in NADPH requirements and regulation in different states of yeast metabolism. Issue 8 (9th August 2018) - Ouyang, Liming; Holland, Petter; Lu, Hongzhong; Bergenholm, David; Nielsen, Jens
Abstract: The Saccharomyces cerevisiae transcription factor (TF) Stb5 is known to be involved in regulating NADPH generation. We explored its role by combining DNA binding studies with transcriptome analysis at four environmental conditions that were selected to cover a range of different metabolic states. Using ChIP-exo, DNA binding targets of Stb5 were found to confirm many previously proposed binding targets, in particular genes encoding enzymes involved in NADPH generation and the pentose–phosphate (PP) pathway. Transcriptome analysis of an STB5 deletion strain revealed transcriptional changes in direct regulation targets of Stb5, including several PP pathway genes as well as additional novel regulatory targets, but interestingly not including the proposed PP pathway flux controlling enzyme Zwf1. Consistently, NADPH levels were found to decrease significantly with STB5 deletion in cultures with aerobic, glucose metabolism. We also found reduced growth for the STB5 deletion strain in similar conditions as those with reduced NADPH levels, supporting a role for Stb5 in NADPH generation through the PP pathway. We finally explored the flux distribution by genome scale modelling simulations and found a decreased flux in both NADPH generating as well as consuming reactions in the STB5 deletion strain. Abstract : The integrated analysis on the data from ChIO-exo, transcriptomes and flux calculations supports a key role of Stb5 in NADPH metabolism and shows the power of system biology methods.